Picea orientalis (L.) Peterm. at Peter the Great Botanic Garden - Firsov Gennadiy; Volchanskaya Alexandra; Orlova Larisa; Tkachenko Kirill (Hortus Botanicus)
Picea orientalis (L.) Peterm. (oriental spruce) (Pinaceae) was introduced into world horticulture by the Peter the Great Botanical Garden and has been mentioned in the catalogues of this garden since 1793. It is one of the tallest trees in the Caucasus and one of the largest trees in the flora of Russia, reaching 50 m in height. The modern collection contains 4 specimens of three samples of this species from the nature of the Caucasus, the last specimens were obtained by plants since 1981. The best specimen reaches 7.65 m in height, with a trunk diameter of 14 cm, with a crown of 3.4 x 3.1 m at the age of about 47 years. In 2023, it formed cones with normally developed seeds for the first time. It was previously noted that this crop was not winter-hardy enough for the conditions of the North-West, periodically froze, but over time it was restored (grown) again. The eastern spruce is a rather original ornamental tree, valuable for modern green construction. In modern conditions of climate warming, this species becomes more promising and relatively new for culture in the North-West of Russia. At present, it has become possible to increase the winter hardiness of this species due to the possibility of growing new adapted individuals of this species from seeds of its own reproduction in the conditions of the North-West of Russia.